2022
DOI: 10.3390/su14010458
|View full text |Cite
|
Sign up to set email alerts
|

Organizational and Personal Factors That Boost Innovation: The Case of Nurses during COVID-19 Pandemic Based on Job Demands-Resources Model

Abstract: Since 2019, the world has been experiencing a pandemic period due to the COVID-19 virus, which has brought the need for organizations in general, healthcare organizations and their professionals in particular, to focus on innovation as a way to fight an utterly unknown virus. Thus, this study aims to understand how nurses and their personal factors (stress, anxiety, work engagement, organizational support) impact their innovative behaviour and innovation outputs, contributing to innovation in the current pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 104 publications
1
22
1
Order By: Relevance
“…In Australia, the implementation of an innovative nurse‐led care model increased compliance with nutritional management guidelines for patients with head and neck cancer, improved nutritional status and treatment completion rates and reduced unplanned hospital admissions as well as care‐related costs (Findlay et al, 2020). Another cross‐sectional survey of frontline nurses in Portugal showed that innovative behaviours and products improved care for patients during the COVID‐19 (Moreno Cunha et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, the implementation of an innovative nurse‐led care model increased compliance with nutritional management guidelines for patients with head and neck cancer, improved nutritional status and treatment completion rates and reduced unplanned hospital admissions as well as care‐related costs (Findlay et al, 2020). Another cross‐sectional survey of frontline nurses in Portugal showed that innovative behaviours and products improved care for patients during the COVID‐19 (Moreno Cunha et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“… 55 , 57 , 66 , 71 Two articles provided evidence that IWB in the service sector is positively impacted by engagement. 47 , 72 Additionally, scholars did not discover a significant link between the positive emotion factor and IWB in the service industry, particularly in the hotel industry. 3 , 54 , 67 …”
Section: Resultsmentioning
confidence: 95%
“…What is interesting in Figure 3 is the growth of articles in 2019 to 2020 are contributed by scholars from European Union countries with seven articles altogether. 47 , 58 , 61 , 62 , 65 67 The increasing number of papers from European Union countries is contributed by the objective of EU2020 strategy which is to develop the European economy based on research and development (R&D), knowledge and innovation. 68…”
Section: Resultsmentioning
confidence: 99%
“…There are other studies that are similar and support this hypothesis. Cunha & Marques (2022) stated that personal factors, including organizational support, can have a positive impact on the innovation outcomes and innovative behavior of nurses during the Covid-19 pandemic. Another similar study is the study by Shabbir et al (2021) which states that good organizational support, together with organizational justice, will result in good work performance for bank employees during the Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%